Improved adaptive routing for networks‐on‐chip. Issue 25 (1st December 2015) - Kumar, M.; Gaur, M.S.; Laxmi, V.; Daneshtalab, M.; Zwolinski, M.; Ko, S.
Abstract : The degree of adaptiveness has a major impact on the performance of an adaptive routing method. An improved turn model‐based routing method that provides a high degree of adaptiveness for a 2D mesh is presented. The proposed method reduces restrictions on the routing turns significantly and hence can provide path diversity using additional routes (both minimal and non‐minimal). Experimental results show that the proposed method provides better performance (average latency and throughput) compared with recent routing methods.